Theoretical and Legal Approaches on Determining the Content of the Notion of “Health Tourism” - A. O. Podzirov (Bulletin of Kharkiv National University of Internal Affairs)
The author has proved the prospects of medical tourism development in Ukraine. The analysis of the concepts of “tourism” and “health tourism” has been carried out; their features have been singled out. The expediency of distinguishing the concept of “health tourism” on “medical” and “health” has been proved. It has been offered to amend the Art. 1 of the Law of Ukraine “On Tourism” by defining the terms of “medical tourism” and “health tourism”.